Kampung Adat Cireundeu: Local Heritage as a Pillar of the Climate Justice - Permana, Fadhil Azhar; Maulana, Fahrulrozi; Ibrahim AM, Fatih Marwan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Kampung Adat Cireundeu is a traditional Sundanese community in West Java, which has successfully maintained its local wisdom and cultural values in harmony with nature. This research aims to examine how environmental care character education is applied in the Cireundeu indigenous community, as well as how local wisdom-based spatial planning supports ecological sustainability. Descriptive qualitative research method was used with data collection techniques through participatory observation, in-depth interviews, and literature study. The results show that the Cireundeu community implements a holistic education system that combines formal and traditional education, with a focus on instilling Sundanese cultural values and environmental awareness. The concept of ‘Gusti nu asih, alam nu ngasah, manusa nu ngasuh’ becomes the foundation in maintaining the balance between humans and nature. The village layout is divided into residential, agricultural, protected forest, and spiritual zones, each of which has a function and strict customary rules to preserve the environment. This research concludes that local wisdom and culture-based character education play an important role in shaping a sustainable and environmentally friendly community. The findings can serve as a model for other communities in integrating local values with sustainable practices.